Standards and programmes designed to mitigate tax evasion: an international appraisal - De Souza, Michelle Adriana (My University, 2017)
As a result of a weakening and slow global economy and rising debt, many foreign governments are finding it difficult to implement strategies to ensure continued inclusive and sustainable growth. It is based on this troubling perspective of global uncertainty that tax authorities worldwide have unanimously persisted in their fight against tax evasion through the under-declaration of income from foreign assets, the illegal movement of money abroad, the misapplication and / or manipulation of transfer pricing legislation and mistreatments of tax treaties. The G20 Leaders together with the Organisation for Economic Co-operation and Development (“OECD”) have developed standards such as the Common Reporting Standard (“CRS”) for the Automatic Exchange of Information (“AEOI”) between tax authorities to enhance the sharing of information and transparency of information between tax authorities worldwide. South Africa has pledged to implement the CRS and automatically share tax information with other jurisdictions on an annual basis in the fight against tax evasion and avoidance. Of significance, in terms of timing for South African tax residents, is that South Africa has undertaken to be one of the early adopters of the CRS and committed to commence the first exchange of information from 2017. In light of the standards and actions coming into place, it has become clear that before long the likelihood of the South African Revenue Services (“SARS”) and the South African Reserve Bank (“SARB”) detecting tax evasion and avoidance is increasingly high. Based on this, non-compliant taxpayers have a limited timeframe to manoeuvre freely in and what may be their last opportunity to voluntarily disclose these assets and the income derived therefrom to SARS and SARB without facing heavier penalties and possible criminal prosecution.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Commerce (specialising in Taxation) Johannesburg, 2017
Keywords: Income tax--Law and legislation--South Africa.; Tax evasion--South Africa